ESTRADIOL AND GNRH ON OVULATION INDUCTION FOR ESTRUS SYNCHRONIZED CROSSBRED COWS - Oliveira, Fabricio Albani (2020)
Estradiol benzoate (EB), estradiol cypionate (EC), and gonadotrophin releasing hormone (GnRH) were evaluated as ovulation inducers for TAI of crossbred lactating cows. In experiment I (n = 45), the follicular dynamics was evaluated, while in experiment II (n = 171) the reproductive efficiency was evaluated. All females were submitted to a synchronization protocol: insertion on day 0 (D0) of intravaginal progesterone-release intravaginal device (PRID; 1g) plus administration of EB 2mg; D8, PRID removal, administration of 0.150mg PGF2α and 400 IU of eCG, and cows were allocated into three treatments: 1) TEB9 – IM administration of 1mg EB on D9 and AI performed 52 hours after PRID removal; 2) TEC – IM administration of 1mg EC on D8 and AI performed 48 hours after withdrawal of PRID; and 3) TGnRH – administration of 100μg GnRH on D10 and AI performed 52 hours after removal of PRID. The follicular growth rate was lower in the EC group (p <0.05). There was no effect of treatments on ovulation and pregnancy rates (p >0.05). The use of EB, EC, and GnRH as ovulation inducers in the TAI protocol did not show marked differences in the evaluated patterns of follicular dynamics and pregnancy.